Robert J. Chalmers: Pioneer Surficial Geologist - Brookes, Ian A. (Geoscience Canada, 2008)
Most Quaternary geologists working in Atlantic Canada view Robert J. Chalmers’ investigations of the surficial geology of New Brunswick for the Geological Survey of Canada (GSC) as seminal contributions. Yet, the fullest biographical information available for Chalmers is a 7-page typescript by E.R. Faribault of the GSC, held at Natural Resources Canada Library in Ottawa. Therefore, it appeared necessary to bring Chalmers’ little-known life, and the variety of his surficial geologic investigations, into the mainstream. Lists of Chalmers’ published works in GSC reports and in periodicals are compiled from all available sources. SOMMAIRE La plupart des géologues du Quaternaire au Canada atlantique voient les études de Robert J. Chalmers sur ‘la géologie en surface’ de Nouveau Brunswick pour le Commission géologique du Canada comme des ouevres séminales. Mais, l’information biographique le plus pleine de Chalmers est un texte bref dactylographié par E.R. Faribault du CGC, tenue à la bibliothèque du Département des Richesses naturelles canadienne à Ottawa. Donc, il apparait nécessaire à porter au premier plan sa vie mal-connue, et le variété de ses oeuvres. Aussi, listes des oeuvres de Chalmers pour le CGC et dans les journaux scientifiques sont ici présen-tent des sources disponsible.